2022
DOI: 10.3390/life12101555
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance in Some Fertility Biomarkers Induced and Changes in Testis Architecture by Chronic Exposure to Various Dosages of Each of Nonylphenol or Bisphenol A and Their Mix

Abstract: This investigation was conducted to demonstrate the potential impacts of different doses of Bisphenol A(BPA) or Nonylphenol (NP) and their mixtures on some biological activities in male albino rats. Seventy male albino rats were allocated to the control group (GI) and were given 1 mL of ethanol. G II and G III were given 100 mg/kg of each of BPA and NP, G IV and G V were given 25 mg/kg of each of BPA and NP, G VI was given a high dose of BPA and NP, and G VII was given a low dose of BPA and NP. All animals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…19 Among the studies performed, significant increases in TNF Alpha, TNF Beta, and Caspase 3 levels were observed in BPA and NP exposure, and histological changes such as decreased spermatozoa in the lumen of seminiferous tubules and impaired germinal epithelium were detected. 16 In the present study, we found that different doses of these EDCs immunohistochemically altered the expression level of RIPK1 in testicular tissue. We used low and high dosages of BPA, NP, and their combined forms in a rat model.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…19 Among the studies performed, significant increases in TNF Alpha, TNF Beta, and Caspase 3 levels were observed in BPA and NP exposure, and histological changes such as decreased spermatozoa in the lumen of seminiferous tubules and impaired germinal epithelium were detected. 16 In the present study, we found that different doses of these EDCs immunohistochemically altered the expression level of RIPK1 in testicular tissue. We used low and high dosages of BPA, NP, and their combined forms in a rat model.…”
Section: Discussionsupporting
confidence: 57%
“…21 Studies have noted apoptosis in germ cells, Sertoli and Leydig cells, and vacuolation in seminiferous tubules. 16,22,23 In a study, apoptotic formations and a significant increase in serum caspase three levels were detected in the germinal cells of rats exposed to 100 mg/kg doses of BPA, NP, and their mixture. 16 According to one study, BPA and NP have harmful effects that are dose-dependent on several parameters, including sperm toxicity, testicular weight, and prostate gland weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations